The Effect of Hospital Service Management Quality on Patient Satisfaction at Siloam Lippo Village Hospital Building B Karawaci - Albert Diaz Pratama; Kayla Putri Legawa; Natasha Waya; Innocentius Bernarto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The development of technology and information increases public understanding, making them more selective in choosing health services. Therefore, hospitals must provide the best service with good management and planning, as well as quality workers. Objective: This study aims to determine and explain the effect of hospital service management quality on patient satisfaction at Siloam Lippo Village Hospital Building B Karawaci, based on a review of literature and previous research. This study applies a basic method in the form of a quantitative descriptive method. The quantitative descriptive method is a systematic approach to answering a problem and gaining a deeper understanding of a phenomenon. This study evaluates the relationship between various aspects of hospital service quality, such as management service quality, technical, empathy, responsiveness, accessibility, responsibility, security, patient involvement, and other elements such as communication, access and waiting time, and quality of care, with patient satisfaction. The results of the analysis show that the majority of these factors have a positive and significant effect on patient satisfaction, except for some elements that do not show a significant effect. This study makes an important contribution to understanding the factors that influence patient satisfaction in hospitals, by highlighting the importance of holistic service quality management to improve patient experience and satisfaction.